Bridging Entrepreneurial Finance in the EU: The New Crowd Funding Regulation - Sasso, Lorenzo (Frontiers in Law, 2023)
Bridging finance to small and medium enterprises (SMEs) is a must in the sustainable economic development of any country. Access to finance is an essential determinant for business start-ups, development and growth for SMEs. In these years, crowd funding digital platforms have flourished fast as an innovative form of financing for SMEs. Their characteristics allow them to perform SME credit risk assessment better and quicker than traditional financial intermediaries. Compared to banks, for instance, crowd funding digital platforms benefit from minimal capital requirements and a flexible organizational structure that, thanks to the new digital technology, can collect and process information and big data much more quickly. To foster the growth of the crowd funding industry in the EU and ensure investor protection, the legislator introduced the European Crowd funding Service Provider Regulation (ECSPR). The new regulation aims to create a standardized regulatory framework by harmonizing the crowd funding services in the common market and facilitating cross-border operations, enhancing investor protection, promoting transparency and ensuring compliance with the regulatory requirements to increase investor confidence. This article discusses the ECSPR’s objectives, requirements and critical provisions. Furthermore, it evaluates the ECSPR’s results against the EU legislator’s initial intents of fostering the growth of the crowd funding industry and enhancing investors’ trust and confidence with protection measures. A balance between these two would be optimal.